Bilateral Naevus of Ota: A Case Report - Çiçek, Demet (Fırat University, 2007)
The naevus of Ota (naevus fusculocoeruleus ophthalmomaxillaris) was first described by the Japanese dermatologist M.T. Ota in 1939. It usually occurs hyperpigmentation in skin areas innervated by the first or the second branch of the trigeminal nevre. The lesions is usually unilateral but is reported %5 bilateral. We report a 32 year-old female who has pigmentation on face and eyes because of the very rare case of bilateral naevus of Ota. ©2007, Firat University, Medical Faculty

Naevus fusculoeruleus ophthalmomaxillaris olarak da bilinen Ota nevus, 1939 yılında Japon dermatolog Ota tarafından tanımlanmıştır []. Trigeminal sinirin 1. ve 2. dallarının innerve ettiği bölgelerdeki deri ve mukozalarda pigmentasyon artışı ile karakterizedir. Lezyonlar genellikle unilateraldir ancak olguların %5’inde bilateral olduğu bildirilmiştir. Yüzünde ve gözlerinde kahverengi lekelenme şikayeti ile polikliniğimize başvuran ve bilateral Ota nevus tanısı alan 32 yaşındaki bayan olguyu nadir görülmesi nedeniyle yayınlamayı uygun bulduk. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Bilateral Ota Nevus Olgusu